Coping with People's Inflation Perceptions During a Currency Changeover - Thomas A. Eife; W. Timothy Coombs (University of Heidelberg, Department of Economics, 2006)
The gap between actual and perceived inflation is one of the more unexpected consequences of the euro changeover in January 2002. In this note we argue that this gap was caused by a lack of preparation and experience of the authorities to appropriately communicate with the public during the changeover. Using principles of crisis communication we identify the mistakes made and give policy recommendations for future changeovers.
Keywords: E50; E60; Y80; 330; crisis communication; transformative explanation; perceived inflation; euro changeover